(3bGfhfLIs - (3eMehO Hf eMeO Hf YeQ, CHh Ydj, TQa GdOjf GdLZejfj GdNhGQRej , J (B618 (3g`s; (3GdLZejfj , eMehO Hf eMeO Hf YeQ, TQa GdOjf CHh Ydj,J (B618 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3agPG eNJUQ eTJed Ydi RHOI eG jLH ENJUGQg ef UfGYI GdWH , GNJUQJg ef cJH GdCbOejf hQJHJg Ydi YTQ ebGdGJ GdebGdI GdChdi ai GdCehQ GdWHjYjI s
(3BNQgG (B:s
(3hCeG GdMdhi aGdYSdi jYjf Ydi GdgVe , hGdYLjfi ZdjX jhdO GdSOhO , hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH Je GdcJGH s
(3fSNI QGHYI cGdSGHbIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B181 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B198s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B180 s
Keywords: (3GdWHs